Bahasa Inggris - Asmawati, Tary; Hidayat, Muhammad; Murialti, Neng (Universitas Muhammadiyah Bengkulu, 2025)
Unemployment is an economic problem that has a direct impact on the welfare of society and the economic stability of a country, including Indonesia. The purpose of this study is to analyze what factors reduce unemployment in the Sumatra Island region using the FD-GMM and Sys-GMM methods, and test the application of Okun’s Law in the Sumatra Island region, the variable used are Economic Growth Rate, Foreign Direct Investment, Domestic Investment, School Partcipation Rate, with dynamic data panel regrission from 154 regencies/cities during the period 2017-2023 using stata 17 software. The result showed that economic growth had a significant negative effect on unemployment, supporting the application of Okun’s Law. However, government capital expenditure shows a significant positive relationship with unwmployment, foreign direct investment (FDI) has a signifcant negative effect, while domestic investment and school participation rate have no significant effect. These findings highlight the need for more effective management of government spending and investment policies that support sustainable job creation in the Sumatra Island region